Infaq dan Larangan Tahlukah dalam QS. Al-Baqarah Ayat 195 Perspektif Tafsir Mufassir Nusantara - Siti Nur Wahyu Ningsih; Safria Andy (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
Muslim society today is faced with the problem of financial management, particularly regarding the distribution of wealth which has two sides: infaq, as a form of constructive expenditure, and tahlukah, namely the destructive use of wealth. These two concepts are reflected in QS. Al-Baqarah: 195 which contains the command to spend infaq in the way of Allah and the prohibition of throwing oneself into destruction. This verse becomes a normative basis in building Islamic financial ethics that touch on spiritual, social, and structural aspects. This study aims to examine the interpretation of Sheikh Abdurrauf as-Singkili in Tarjumān al-Mustafīd and Imam Nawawi al-Bantani in Mir’āt al-Labīb on the verse in the context of wealth management. Using descriptive qualitative methods and content analysis, this study explores the meaning of infaq and tahlukah in the socio-economic life of Muslims in the archipelago. The results show that infaq is seen as a form of obedience and social concern, while tahlukah is a result of stinginess and negligence towards social obligations. Abdurrauf emphasized a spiritual and moral approach, while Nawawi emphasized the structural and practical dimensions of wealth management, including financing education, mosques, and Islamic outreach. In conclusion, Nusantara interpretation of Islamic thought can ground Quranic values in local contexts and contribute to shaping contextual, moderate, and equitable Islamic financial ethics.